2004
DOI: 10.1146/annurev.phyto.42.040803.140421
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Acquired Resistance

Abstract: Systemic acquired resistance (SAR) is a mechanism of induced defense that confers long-lasting protection against a broad spectrum of microorganisms. SAR requires the signal molecule salicylic acid (SA) and is associated with accumulation of pathogenesis-related proteins, which are thought to contribute to resistance. Much progress has been made recently in elucidating the mechanism of SAR. Using the model plant Arabidopsis, it was discovered that the isochorismate pathway is the major source of SA during SAR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
1,753
3
52

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,471 publications
(1,894 citation statements)
references
References 125 publications
29
1,753
3
52
Order By: Relevance
“…It has been suggested that disease resistance is associated with fitness costs and that plants have evolved inducible defense mechanism because it is too costly to have defense responses switch on all the time [5,75]. For instance, overexpression of AtWRKY6, AtWRKY18, AtWRKY53 or AtWRKY70 always resulted in small stunted transgenic plants [50,54,76].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that disease resistance is associated with fitness costs and that plants have evolved inducible defense mechanism because it is too costly to have defense responses switch on all the time [5,75]. For instance, overexpression of AtWRKY6, AtWRKY18, AtWRKY53 or AtWRKY70 always resulted in small stunted transgenic plants [50,54,76].…”
Section: Discussionmentioning
confidence: 99%
“…ZB8 is a rice PAL gene and has been shown to be induced under wounding and fungal cell wall elicitor treatment [71]. Peroxidase genes are also a class of protective genes that are induced in plant defense response [5]. One rice peroxidase gene, POX22.3 has been shown to be predominantly induced upon X. oryzae pv.…”
Section: Overexpression Of Oswrky03 In Rice Leads To Induced Expressimentioning
confidence: 99%
See 1 more Smart Citation
“…ROS along with NO (nitric oxide) induce HR (hypersensitive response)-mediated cell death (Delledonne et al 2001). ROS in association with salicylic acid are proposed to mediate the establishment of systemic defenses (Durrant and Dong 2004). The cytological studies have revealed that ROS and NO are associated with cell death adjacent to infected cells and so that both signals modulate each other's accumulation (Tada et al 2004).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…The R-proteins mediate a defense reaction culminating in hypersensitive response (HR) and eventually a localized cell death at the site of infection [1,2]. Further, the pathogenesis-related (PR) genes are induced in the host plant accelerating a systemic disease resistance against the pathogens throughout the plant [5].…”
Section: Introductionmentioning
confidence: 99%